RESTful Web APIs - Richardson, Leonard 1979- (O'Reilly, 2013)
The popularity of REST in recent years has led to tremendous growth in almost-RESTful APIs that don't include many of the architecture's benefits. With this practical guide, you'll learn what it takes to design usable REST APIs that evolve over time. By focusing on solutions that cross a variety of domains, this book shows you how to create powerful and secure applications, using the tools designed for the world's most successful distributed computing system: the World Wide Web. You'll explore the concepts behind REST, learn different strategies for creating hypermedia-based APIs, and then put everything together with a step-by-step guide to designing a RESTful Web API. Examine API design strategies, including the collection pattern and pure hypermedia Understand how hypermedia ties representations together into a coherent API Discover how XMDP and ALPS profile formats can help you meet the Web API "semantic challenge" Learn close to two-dozen standardized hypermedia data formats Apply best practices for using HTTP in API implementations Create Web APIs with the JSON-LD standard and other the Linked Data approaches Understand the CoAP protocol for using REST in embedded systems.
Includes index. - Online resource; title from title page (Safari, viewed December 21, 2016)
Keywords: Application program interfaces (Computer software); Representational State Transfer (Software architecture); Web site development; Web sites -- Design; Interfaces de programmation d'applications; REST (Architecture logicielle); Sites Web; Développement; Sites Web; Conception; APIs (interfaces); Web sites; Design